Schizophrenia and intersubjectivity: an embodied and enactive approach to psychopathology and psychotherapy - Fuchs, Thomas; Röhricht, Frank (Philosophy, psychiatry, & psychology, 2017)
Current phenomenological approaches consider schizophrenia as a fundamental disturbance of the embodied self, or a disembodiment. This includes (1) a weakening of the basic sense of self, (2) a disruption of implicit bodily functioning, and (3) a disconnection from the intercorporeality with others. As a result of this disembodiment, the pre-reflective, practical immersion of the self in the shared world is lost. Instead, the relationship of self and world is in constant need of being reconstructed by deliberate efforts, leading to the growing perplexity and hyperreflexive ruminations that are found in schizophrenia patients. The paper distinguishes different levels of self-experience and relates them to the psychopathology of schizophrenia, taking particularly into account disturbances of self-awareness, perception, action, and intersubjectivity. On this basis, psychotherapeutic approaches based on body awareness and movement techniques are outlined that are suited to foster self-management and enable patients to re-establish a more stable and coherent sense of self.
Gesehen am 28.10.2020